2015
DOI: 10.2527/jas.2015-9212
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters and genetic trends for reproductive traits and weaning weight in Tabapuã cattle1,2

Abstract: The Tabapuã breed is a beef cattle Brazilian breed known for its sexual precocity and desirable characteristics for tropical conditions. However, this is a newly formed breed and few studies have been conducted regarding genetic parameters and genetic trends for its reproductive traits. The objective of the present study was to estimate the genetic parameters, genetic trends, and relative selection efficiency for weaning weight adjusted to 210 d of age (W210), age at first calving (AFC), average calving interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
4
7
0
2
Order By: Relevance
“…For W210, the direct heritability estimates were in agreement with those obtained by Zuin et al (2012), Bernardes et al (2015), and Pires et al (2016) for the Nelore, Tabapuã, and Canchim breeds. Lopes et al (2016), Vargas et al (2014), and Mota et al (2013) observed h 2 d for W450 in Nelore, Brahman, and Simmental animals of 0.52 ± 0.02, 0.22 ± 0.06, and 0.27, respectively.…”
Section: Resultssupporting
confidence: 82%
“…For W210, the direct heritability estimates were in agreement with those obtained by Zuin et al (2012), Bernardes et al (2015), and Pires et al (2016) for the Nelore, Tabapuã, and Canchim breeds. Lopes et al (2016), Vargas et al (2014), and Mota et al (2013) observed h 2 d for W450 in Nelore, Brahman, and Simmental animals of 0.52 ± 0.02, 0.22 ± 0.06, and 0.27, respectively.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, in the present study, the estimated heritability of GL (0.081) was consistent with that in in Japanese Black cows (0.080) [28], whereas it is lower (0.037) in the Rubia Gallega breed [15]. In our study, AFC was the reproductive trait that demon strated the highest heritability (0.180), which was consistent with (0.215) in Japanese Black cattle [18], higher heritability (0.28) in Angus heifers [8], and lower heritability (0.09) in the Tabapuã beef breed [29].…”
Section: F-value P-value F-value P-value F-value P-value F-value P-vasupporting
confidence: 83%
“…This estimate was higher than most of the consulted literature for the Nelore breed [4,[29][30][31]. Martínez-Velázquez et al [32] and Bernardes et al [33] obtained heritability estimates of 0.28 AE 0.06 and 0.09 AE 0.02 in Angus heifers and Tabapuã beef cattle, respectively.…”
Section: Traitsmentioning
confidence: 66%